2020
DOI: 10.1186/s12887-020-02186-7
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalizations for viral respiratory infections in children under 2 years of age: epidemiology and in-hospital complications

Abstract: Background Viral respiratory infections (VRIs) are a frequent cause of hospitalization in children under 24 months of age. A history of prematurity or heart disease may be a risk factor for complications in patients hospitalized for VRI. The objective was to describe epidemiological data for children hospitalized for IRV and aged 1 to 24 months and to identify risk factors for the presence of in-hospital complications and mortality over a period of 5 years. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 28 publications
2
5
0
Order By: Relevance
“…9 In a large population study of 66,304 hospital admissions of children 1-24 months old, Zuritz-Cruz et al reported a mean length of stay of 4.1 ± 4.4 days for a respiratory viral infection. 8 Thus, hospital length of stay, a surrogate for illness severity, in our single ventricle cohort is comparable to previous studies and relatively brief during the periods of Glenn circulation and Fontan circulation.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…9 In a large population study of 66,304 hospital admissions of children 1-24 months old, Zuritz-Cruz et al reported a mean length of stay of 4.1 ± 4.4 days for a respiratory viral infection. 8 Thus, hospital length of stay, a surrogate for illness severity, in our single ventricle cohort is comparable to previous studies and relatively brief during the periods of Glenn circulation and Fontan circulation.…”
Section: Discussionsupporting
confidence: 87%
“…5,6 Simple and complex forms of CHD are risk factors for viral-related hospital admissions and increased hospital length of stay for viral-related admissions. 7,8 Focusing on patients with single ventricle CHD, one recent study showed that upper and lower respiratory infections are the most common causes of non-cardiac hospital admissions. 9 However, few data exist on how respiratory viruses influence clinical presentations, hospital admissions, and hospital length of stay for patients with single ventricle CHD.…”
mentioning
confidence: 99%
“…The rates of these complications and mortality are much higher than reported in the literature. 38 , 39 …”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the findings of other studies in which younger infants were at higher risk of need for supplemental O 2 administration and PICU admission. 11 , 21 , 22 , 23 , 24 , 25 , 26 These clinical data are correlated quite precisely with improved understanding of the infant's immune system, in which the innate immune response against RSV, especially the interferon response, does not appear to be protective until after 6 months of age. 27 , 28 …”
Section: Discussionmentioning
confidence: 78%